2017
DOI: 10.1016/j.jmoldx.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing of 51 Genes Involved in Primary Electrical Disease

Abstract: Primary electrical disease (PED) is characterized by cardiac arrhythmias, which can lead to sudden cardiac death in the absence of detectable structural heart disease. PED encompasses a diversity of inherited syndromes, predominantly Brugada syndrome, early repolarization syndrome, long QT syndrome, short QT syndrome, arrhythmogenic right ventricular cardiomyopathy, and catecholaminergic polymorphic ventricular tachycardia. To overcome the diagnostic challenges imposed by the clinical and genetic heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
16
1
Order By: Relevance
“…Based on these findings, genes expressed during embryogenesis in precursors of thyroid and heart are promising candidate genes to be considered for their involvement in the pathogenesis of TD. The variant detected in our patients’ family has been so far reported to be causative in an individual affected with accessory atrioventricular connection and one individual referred for primary electrical disease testing [ 9 , 10 ]. However, neither this variant nor any other mutation in NKX2-5 gene were so far detected in patients with THA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, genes expressed during embryogenesis in precursors of thyroid and heart are promising candidate genes to be considered for their involvement in the pathogenesis of TD. The variant detected in our patients’ family has been so far reported to be causative in an individual affected with accessory atrioventricular connection and one individual referred for primary electrical disease testing [ 9 , 10 ]. However, neither this variant nor any other mutation in NKX2-5 gene were so far detected in patients with THA.…”
Section: Discussionmentioning
confidence: 99%
“…After inverse centrifuging the serum tubes, we were able to recover white blood cells and obtained sufficient quality and amount of DNA. After informed consent and permission of his spouse post-mortem genetic analysis was performed on this sample using next-generation sequencing panels of known cardiomyopathy and primary arrhythmia genes (each n=51 genes) (13). Segregation analysis showed that the KCNQ1 variant was inherited from the proband's mother and transmitted to the proband's daughter.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Genomic DNA was extracted from whole blood using standard procedures. Genetic testing of SCN5A was performed using an in-house developed cardiac arrhythmia gene panel (14). Sanger sequencing was used to validate the variants and perform familial segregation analysis.…”
Section: Mutation Analysis Of Scn5amentioning
confidence: 99%